Effects of Peanut (Arachis Hypogaea L.) and Its Combination with Propranolol in Isoproterenol Induced Myocardial Damage in Rats - Naz, Farah; Jahan, Nasim; Sultana, Nayma; Nabi, Mohammad Hayatun (Journal of Bangladesh Society of Physiologist, 2016)
Background: Ischemic heart disease is the interruption of blood supply to the heart causes several biochemical alterations which may lead to cardiac dysfunction and ultimately cell death. Medicinal plants and plant based foods such as peanut (Arachishypogaea L.) have received great attention for their salutary effects and potential to treat many aspects of ischemic heart disease due to their antioxidant property. Objective: To observe the effects of peanut (Arachishypogaea L.) and its combination with propranolol in isoproterenol induced myocardial damage in rats. Method: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka in 2012. For this purpose, 20 Wistar albino rats, age 85 to 100 days, weighing 120 to 150g (initial body weight) were included in the peanut treated group.They were sub-divided into CT-P (Cardiotoxic group with isoproterenol after peanut treatment) and CT-C (Cardiotoxic group with isoproterenol after combined treatment of peanut and propranolol). Age and weight matched 30 Wistar albino rats without any peanut supplementation were taken and sub-divided into three sub-groups, BC (Baseline control), CT (Cardiotoxic group with isoproterenol) and CT-PRO (Cardiotoxic group with isoproterenol after propranolol treatment). Each sub-group consisted of 10 rats. After taking final body weight all the rats were sacrificed on 22nd day. Blood was collected from heart & supernatant serum was preserved in deep freeze until analysis. For assessment of myocardial damage, some cardiac biomarker enzymes, like serum CK-MB & LDH were estimated by using immunoassay method. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. Result: In this study, percent change from initial body weight to final body weight was significantly (p<0.01) lower both in CT-P and CT-C as compared to that of BC. Again, the mean serum CK-MB and LDH levels were significantly (p<0.01) higher in CT, CT-PRO, CT-P & CT-C in comparison to that of BC. On the other hand, the serum CK-MB and LDH levels were lower in CT-PRO, CT-P and CT-C when compared to that of CT though the differences were statistically significant (p<0.01, p<0.05) in case of CT-PRO and CT-C but not significant in case of CTP. Again, the values were also significantly lower in CT-C (p<0.01,p<0.05) as compared to that of CTP. Conclusion: The present study revealed that peanut can lower serum CK-MB & LDH levels towards normal in isoproterenol induced myocardial damaged rats. However, the combined therapy of peanut with propranolol showed synergistic effect on lowering serum CK-MB & LDH levels. Bangladesh Soc Physiol. 2016, December; 11(2): 74-79